2016
DOI: 10.1513/annalsats.201511-782oc
|View full text |Cite
|
Sign up to set email alerts
|

Resilience in Survivors of Critical Illness in the Context of the Survivors’ Experience and Recovery

Abstract: Rationale: Post-intensive care syndrome (PICS), defined as new or worsening impairment in cognition, mental health, or physical function after critical illness, is an important development in survivors. Although studies to date have focused on the frequency of these impairments, fundamental questions remain unanswered regarding the survivor experience and the impact of the critical illness event on survivor resilience and recovery.Objectives: To examine the association between resilience and neuropsychological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
138
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(148 citation statements)
references
References 65 publications
4
138
1
3
Order By: Relevance
“…Individualised discharge planning decreases hospital readmissions in medical patients,39 and could address many of the issues occurring in the ‘complex health and psychosocial needs’ context if introduced at the system level. Screening for low resilience and intervening to support patients might also be a useful part of this process,40 and could address the ‘struggling to cope’ described by many participants. This is recognised as useful in other populations such as cancer 41…”
Section: Discussionmentioning
confidence: 99%
“…Individualised discharge planning decreases hospital readmissions in medical patients,39 and could address many of the issues occurring in the ‘complex health and psychosocial needs’ context if introduced at the system level. Screening for low resilience and intervening to support patients might also be a useful part of this process,40 and could address the ‘struggling to cope’ described by many participants. This is recognised as useful in other populations such as cancer 41…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that these individuals were more resilient,51 or that they had pre-existing physical illness that affected their adaptation to post-ARDS physical outcomes. The latter explanation may be supported by these patients being older and less likely to reside independently at home than patients in the subtype with severe physical and severe mental impairment.…”
Section: Discussionmentioning
confidence: 99%
“…The Joint Commission has recommended that all hospital discharge summaries include the "reason for hospitalization" and "significant findings" (7). This recommendation aligns with qualitative studies of survivors of critical illness that revealed that survivors demand, yet are often unaware of, the details of their critical illness (8,9). Despite the Joint Commission's recommendations, a review found that a primary diagnosis and a hospital course were present in only 17.5 and 14.5% of discharge summaries, respectively (10).…”
mentioning
confidence: 92%